Anti-de Sitter strictly GHC-regular groups which are not lattices - Lee, Gye-Seon; Marquis, Ludovic (Transactions of the American Mathematical Society, 2019)
For , we exhibit examples of strictly GHC-regular groups which are not quasi-isometric to the hyperbolic space , nor to any symmetric space. This provides a negative answer to Question 5.2 in a work of Barbot et al. and disproves Conjecture 8.11 of Barbot-Mérigot [Groups Geom. Dyn. 6 (2012), pp. 441-483].
Gesehen am 29.07.2019